Anticancer and Antioxidant Activities of Haplanthodes verticillatus: Insights from In Vitro and In Vivo Studies - Joshi, Swati; Shrivastava, Sarika; Banweer, Jitendra (Journal of Neonatal Surgery, 2025)
Breast cancer (BC) continues to be the foremost cause of cancer-related fatalities in women, with triple-negative breast cancer (TNBC) presenting distinct therapeutic difficulties owing to its aggressive characteristics and restricted therapy alternatives. This study assesses the anticancer efficacy of the ethyl acetate extract derived from Haplanthodes verticillatus, an indigenous plant recognized for its traditional therapeutic applications. The antioxidant activity of the extract was evaluated by the DPPH radical scavenging assay, demonstrating efficacy similar to ascorbic acid with an IC₅₀ of 63.53 µg/mL. In vitro cytotoxicity assays on MDA-MB-231 breast cancer cells demonstrated a dose-dependent decline in cell viability, with an IC₅₀ value of roughly 130 µg/mL. Microscopic investigations revealed apoptosis-like morphological alterations in treated cells. A xenograft mouse model was utilized in vivo to evaluate the extract's impact on tumor volume and weight. The ethyl acetate extract exhibited substantial, dose-dependent tumor inhibition, with the high-dose cohort attaining tumor reductions akin to those produced by cisplatin, a conventional chemotherapeutic drug. Moreover, the extract demonstrated enhanced tolerability, as indicated by better body weight preservation in treated mice compared to that administered cisplatin. Statistical analyses validated the extract's effectiveness and dose-dependent effects on multiple parameters, including tumor volume, tumor weight, and alterations in body weight. The results underscore the therapeutic promise of Haplanthodes verticillatus as a natural anticancer drug, demonstrating significant effectiveness and decreased systemic toxicity.